Impact of urban morphological changes on traffic performance of Jadriyah intersection - Dhirgham Alobaydi; Hasan Al-Mosawe; Ishraq M. Lateef; Amjad H. Albayati (Cogent Engineering, 2020)
The realization of the nexus between morphological changes and road intersection performances remains a challenge in urban studies. Despite the effort spent on minimizing the traffic associated problems (such as congestion and delay) in urban intersections, namely using roundabouts, signalized intersections, and actuated traffic signal controls, there are still traffic performance inefficiencies within intersections. Traffic congestion in the intersection arises for two reasons, namely by densification formed in the surrounding area and by the lack of effective traffic management. In this paper, a morphological analytical approach was adopted to explain the urban intersection changes for a 1 sq. km study area within Jadriyah neighborhood. The study spans three historical phases (1999, 2009, and 2019) and describes the changes to urban morphology by integrating land-use development with traffic data. Problems regarding urban variation in this prominent intersection were measured and then compared in terms of the Level-of-Service (LOS). The deployment of measurement and analytical methods include two sets of measurements: firstly, the study of the morphology of urban form structures, and secondly the data analysis of volume, pedestrian movement, saturation flow, and signal timing during peak hours whilst counting the daily trips generated for each type of changed land use pattern. Analysis of the collected data revealed that the urban morphology of transformed land use over time impacted the traffic volume for each phase on the level of intersection performance. Results thus showed a considerable decline of the urban intersection LOS in Jadriyah neighborhood; the uncontrolled land use expansion led to an increase in the peak volume at a rate of 155 veh/hr per year, whilst the percentage increase in pedestrians was 200% per hour. The paper concluded that ignoring densification and land use development at the urban design level over time has given rise to real impact, whether increasing traffic saturation or delay, on the performance of intersections and thus influence the transportation planning level.